Acetaminophen pharmacokinetics in severely obese adolescents and young adults. Issue 1 (28th November 2018) - Hakim, Mohammed; Anderson, Brian J.; Walia, Hina; Tumin, Dmitry; Michalsky, Marc P.; Syed, Ahsan; Tobias, Joseph D.
Abstract: Background: Intravenous acetaminophen is commonly administered as an adjunctive to opioids during major surgical procedures, but neither the correct pharmacokinetic size descriptor nor the dose is certain in severely obese adolescents undergoing bariatric surgery. Methods: Adolescents, 14‐20 years of age, with a body mass index (BMI) ≥95th percentile for age and sex or BMI ≥40 kg·m −2, presenting for laparoscopic or robotic assisted or vertical sleeve gastrectomy were administered intravenous acetaminophen (1000 mg) following completion of the surgical procedure. Venous blood was drawn for acetaminophen assay at eight time points, starting 15 minutes after completion of the infusion and up to 12 hours afterward. Time‐concentration data profiles were analyzed using nonlinear mixed effects models. Parameter estimates were scaled to a 70‐kg person using allometry. Normal fat mass was used to assess the impact of obesity on pharmacokinetic parameters. Results: The study cohort comprised 11 female patients, age 17 SD 2 years with a weight of 125 SD 19 kg and a mean BMI of 46 SD 5 kg·m −2 . The plasma acetaminophen serum concentration was 17 (SD 4) μg·mL −1 at 10‐20 minutes after completion of the infusion and 5 (SD 6) μg·mL −1 at 80‐100 minutes. A two‐compartment model, used to investigate pharmacokinetics, estimated clearance 10.6 (CV 72%) L·h·70 kg −1, intercompartment clearance 37.3 (CV 63%) L·h·70 kg −1, central volume of distribution 20.4 (CV 46%) L·70 kg −1, and peripheral volume of distribution 16.8 (CV 42%) L·70 kg −1 . Clearance was best described using total body weight. Normal fat mass with a parameter that accounts for fat mass contribution (Ffat) of 0.88 best described volumes. Conclusion: Current recommendations of acetaminophen to a maximum dose of 1000 mg resulted in serum concentrations below detection limits in all patients within 2 hours after administration. Dose is better predicted using total body mass with allometric scaling.